The association of serum vitamin D and calcium level with febrile convulsions - S. M. Al-Ashou; O. M. Alashou; Y. T. Azeez (Regulatory Mechanisms in Biosystems, 2025)
Febrile convulsion s are among the leading public health problem s that affect children between 6 months and 5 years of age , and the effect of this condition on their lives and its exact cause are not fully understood . M any risk factors have been under researched. Among th e possible factors are the vitamin D and calcium level s . The aim of this study is to determine the association of febrile convulsion with the level of vitamin D and calcium. The study included 40 children with febrile co n vulsion as a case group and 40 children with fever (>38.5 °C) without convulsion as the control group. Blood samples were taken from all the participants , put into gel tube s , then the blood was centrifuge d to separate the sample s and collect the serum . T hen the serum level of vitamin D and calcium level w ere measured. In the cases group , 75% were male and only 25% were female. There w ere significant differen ces between the groups in the serum level of vitamin D and calcium with P -value of P < 0.0001, P < 0.008 0 , respectively . The majority of patients in the f ebrile convulsion group (52.5%) ha d vit a min D deficiency. There is a significant effect of vitamin D deficiency and low calcium level on the occurrence of febrile convulsion in children.